2003
DOI: 10.1073/pnas.0730772100
|View full text |Cite
|
Sign up to set email alerts
|

Posterior parietal cortex and the filtering of distractors

Abstract: Neural systems for visual processing can focus attention on behaviorally relevant objects, filtering out competing distractors. Neurophysiological studies in animals and brain imaging studies in humans suggest that such filtering depends on top-down inputs to extrastriate visual areas, originating in structures important for attentional control. To test whether the posterior parietal cortex may be a necessary source of signals that filter distractors, we measured the ability of a patient with bilateral parieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(97 citation statements)
references
References 88 publications
(118 reference statements)
9
86
0
2
Order By: Relevance
“…Anatomical studies have found multiple reciprocal neural pathways between the parietal cortex and visual processing areas, and these pathways may govern such control (50-53). Our results are consistent with lesion studies of visual attention (54) indicating that the posterior parietal cortex interacts with the response of neurons in the visual areas in ways that may fundamentally influence object representations. At present a direct functional connection and interaction between the posterior temporoparietal region and the color region(s) in color perception has not been established.…”
Section: Discussionsupporting
confidence: 81%
“…Anatomical studies have found multiple reciprocal neural pathways between the parietal cortex and visual processing areas, and these pathways may govern such control (50-53). Our results are consistent with lesion studies of visual attention (54) indicating that the posterior parietal cortex interacts with the response of neurons in the visual areas in ways that may fundamentally influence object representations. At present a direct functional connection and interaction between the posterior temporoparietal region and the color region(s) in color perception has not been established.…”
Section: Discussionsupporting
confidence: 81%
“…are attributable to involvement of dorsal parts of pulvinar, which is known in primates to have neurons with bilateral receptive fields (15) and reciprocal connections with posterior parietal cortex (16). Indeed, a patient with bilateral parietal lobe damage has also been shown to perform poorly on the same filtering task used here (42).…”
Section: Discussionmentioning
confidence: 98%
“…We concluded that this group of patients had difficulties either with segmenting new from old, or with disengaging from old information after possibly successful segmentation [compare with Petersen et al, 1989;Posner et al, 1984]. Interestingly, Friedmann-Hill et al [2003] report on a patient (R.M.) with bilateral posterior parietal damage (mainly BA7 and 39), who was severely impaired at ignoring distractors when having to identify a target, even though this target was always presented at the same location.…”
Section: Posterior Parietal Functionmentioning
confidence: 99%